Investigation and analysis of influencing factors on the economic burden of varicella disease in Qingyang, China, 2024 - Beiqin Liu; Xueping Li; Huailu Shi; Lin Yuan; Yongfeng Jing; Yuelong Hui; Meimei Xu; Yan Zhang; Kangjun Zhao; Qiqi Sun; Jingyu Fan; Mingyu Yang (Human Vaccines & Immunotherapeutics, 2025)
This study aims to evaluate the economic burden and associated determinants of varicella cases in Qingyang City, Gansu Province, thereby informing the formulation and effectiveness evaluation of varicella prevention and control strategies. Based on socioeconomic and geographic characteristics, varicella cases reported in 2024 from Xifeng District, Heshui County, and Zhenyuan County were selected for cross-sectional surveys. The direct and indirect economic burdens were analyzed using Excel 2010 and SPSS 20.0 software. Univariate analysis (Wilcoxon/Kruskal-Wallis tests) was conducted to identify factors associated with economic burden, subsequently, binary Logistic regression was employed for multivariate analysis of significant variables. A total of 1,010 varicella cases were analyzed. Clinical characteristics revealed a mean disease duration of 10.33 ± 2.45 days and work loss time of 9.45 ± 4.38 days. Healthcare utilization included an average of 1.80 ± 1.15 medical visits and caregiver duration of 9.37 ± 2.46 days. The overall economic burden amounted to $283,428 (US), resulting in a per capita burden of $256 (IQR: $212–$345). Per capita total economic burdens for mild, moderate-severe, and hospitalized varicella cases were calculated as $172, $257 and $487, respectively (χ2 = 205.730, p < .001); for cases with 0-dose, 1-dose and 2-dose varicella vaccination histories was $286, $172 and $180, respectively(χ2 = 45.507, p < .001); urban versus rural case burden were identified as $277 and $287, respectively (Z = −2.316, p < .05), indicating statistically significant differences across these data sets. The direct economic burden was $95,590, and the indirect economic burden was $187,837. Factors influencing the economic burden included fever severity, the number of rashes, case type, residence type, presence of complications, and varicella vaccination history. Varicella imposes a considerable economic burden in Qingyang, with significant variations associated with vaccination status. The low coverage of varicella vaccination underscores the urgent necessity to implement targeted vaccination strategies and enhance public health education aimed at reducing disease-related costs.